KEEFEKTIFAN TEKNIK KNOW, WHAT, LEARN (KWL) DALAM PERKULIAHAN MEMBACA MAHASISWA PRODI PBSI FKIP UNTIDAR TAHUN AJARAN 2016/2017 - Ayu Wulandari (Universitas Tidar, 2017)
The aims of this research are: (1) prove the significant difference between the result of students’ reading comprehension using KWL technique and the students without KWL technique and (2) prove the effectiveness of KWL technique in reading class. This research applied quasi experiment with Randomized Pretest-Posttest Control Group Design. The populations were the second semester students of Indonesian education and literature study program in the academic year of 2016/2017. Test was used as the instrument of this research. Then, the data was analyzed by using T-test. The results of the study show that (1) there is a difference on the students’ reading comprehension result using KWL and the students without KWL technique. It is shown by Sig value (2-tailed) in experiment class posttest and control class is less than 0.050. (2) KWL technique is effective to be used in reading class.Keywords: reading, KWL technique.